New Licensing Models for Online Music Services in the European Union: From Collective to Customized Management - Mazziotti, Giuseppe (The Columbia Journal of Law & the Arts, 2011)
A few years after the enactment and the implementation in the Member States of the European Union of the most comprehensive directive for the harmonization of national copyright laws in the so-called “Information Society”, the European Commission started reviewing how copyright and related rights were being commercially exploited in the digital environment. Unsurprisingly, in 2005 the Commission eventually realized that copyright management gave rise to licensing practices that segmented the so-called “Internal Market” on a strictly in-territorial basis, in spite of the borderless nature of Webbased environments. From then onwards, the Commission has been in search of solutions to tackle economic inefficiencies stemming from territorial restrictions in copyright management and to eventually boost the growth of legitimate online content services, starting with music services.